High-performance flexible thermoelectric generator by control of electronic structure of directly spun carbon nanotube webs with various molecular dopants. Issue 30 (17th July 2017) - An, Cheng Jin; Kang, Young Hun; Song, Hyeonjun; Jeong, Youngjin; Cho, Song Yun
Abstract : Thermally treated carbon nanotube webs for effective n-type doping are used for a flexible thermoelectric generator with a high power output. Abstract : The development of n-type polymers and composites to pair with their p-type counterparts in current flexible thermoelectric (TE) generators is crucial to reach the full potential of these devices. However, this development has lagged behind because of difficulties associated with n-type doping of organic semiconductors. Our study focused on the doping characteristics of directly spun carbon nanotube (CNT) webs using various n-type dopants in combination with thermal desorption of oxygen from the CNT web surface for more effective n-type doping. Annealing of the CNT web followed by treatment with 2 mg mL −1 benzyl viologen (BV) resulted in a maximum power factor of 3103 μW m −1 K −2, which was superior to that of a BV-treated pristine CNT web without thermal annealing (1901 μW m −1 K −2 ). This value is the highest among organic TE materials and similar to that of the most promising inorganic material, Bi2 Te3 at room temperature. In addition to the effect of BV dopants on the electrical properties, the thermal diffusion property of the BV-doped CNT web was analyzed using the finite element method. The dopant coating on the CNT bundle efficiently suppressed the phonon transfer along the CNT web direction, which led to a reduction of the thermal conductivity of the CNT web. As a counterpart for the n-type CNT web, p-type TE materials with a thermal power of 2252 μW m −1 K −2 were also prepared using molecular dopants of 2, 3, 5, 6-tetrafluoro-7, 7, 8, 8-tetracyanoquinodimethane. Finally, a p–n junction-type TE module with an unprecedented power density of 1.18 mW cm −2 was fabricated based on the development of these competitive n-type TE materials.